CHALLENGES OF SSF PROCESS FOR PEA AND WHEAT BRAN VALORIZATION USING TRICHODERMA SPP. FOR BIOCONTROL AGENT PRODUCTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Fungal strain Trichoderma spp. is a known bio control agent (BCA), which are difficult to obtain using more prevalent industrial-scale biofermentation methods such as submerged fermentation (SmF) However, difficult up-scalable solid-state fermentation (SSF) are appropriate for such BCA production. An automated semi-rotating drum bioreactor was developed and built to explore SSF scale-up using pea and wheat bran as substrates to valorise food-industry by-products into viable BCA ‘s. Estimation of biomass using CO2/O2 analysis in exhaust gasses revealed that mix of pea and wheat bran can produce a viable BCA ‘s using gentle mixing technique with possibilities of industrial scale-up